The clinical effect of a strategy called transcystic gallbladder-preserving cholecystolithotomy based on endoscopic retrograde cholangiopancreatography for cholecystolithiasis: A retrospective study from a single center - Yang, Zhenzhen; Hong, Junbo; Zhu, Liang; Zhang, Cheng; Zhou, Xiaojiang; Li, Guohua; Zhu, Yong; Liu, Zhijian; Zhou, Xiaodong; Chen, Youxiang (Frontiers in Surgery, 2023)
Abstract Background: Choledocholithiasis complicated with cholecystolithiasis is a common disease. This study explores a novel strategy, called ERCP-based transcystic gallbladder-preserving cholecystolithotomy, for the simultaneous removal of common bile duct stones and gallbladder stones. Methods: From December 2018 to June 2021, all patients with cholecystolithiasis and common bile duct stones who met the criteria for gallbladder preservation in our hospital were included in the study and prospectively followed up. Results: We included 48 patients, including 20 patients with acute biliary pancreatitis. All patients successfully underwent ERCP to remove common bile duct stones. One patient had gallbladder perforation during gallbladder-preserving cholecystolithotomy. The guide wire successfully entered the gallbladder, and the transpapillary gallbladder metal-covered stent was successfully placed in 44 patients. The technical success rate was 91.67% (44/48). All stones were removed in 34 patients, for a clinical success rate of 77.27% (34/44). The total postoperative complication rate was 6.25% (3/48), with 2 cases of pancreatitis (4.17%) and 1 case of cholangitis (2.08%). Three patients were lost to follow-up. Among the 31 patients who were followed up for a mean of 27 months (6-40), 5 patients (16.13%) experienced gallstone recurrence. The recurrence rates at 12 months, 18 months, 24 months, 30 months and 36 months were 0%, 3.23%, 6.45%, 12.9%, and 16.13%, respectively. Conclusion: For patients with cholecystolithiasis and common bile duct stones, ERCP-based transcystic gallbladder-preserving cholecystolithotomy without gallbladder incision can preserve gallbladder structure, and this procedure is safe and feasible for the protection of gallbladder function. Clinical trial registration: The study was registered in the Chinese Clinical Trial Registry, and the registry number is ChiCTR1900028006.